2018
DOI: 10.18295/squmj.2018.18.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Critically-Ill Patients at Two Tertiary Care Hospitals in Sudan

Abstract: Most of the patients admitted to the ICUs were middle-aged females with no known underlying comorbidities. Larger studies are necessary to provide a comprehensive understanding of the critical care needs of Sudanese hospitals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 13 publications
3
7
0
2
Order By: Relevance
“…In addition, our data shows that more than half of patients admitted from the emergency room, The present results are in the same line with (Amalraj et al, 2017) who reported that most of their patients were admitted to ICU directly from the emergency room and a few were admission in ICU from the wards/rooms. Regarding comorbidities, our present study shows that the majority of patients had no identifiable comorbidities prior to ICU admission, this finding congruence with a prospective observational study by (Sulieman, et al, 2018) who found that majority of patients had no comorbidities before admission to the ICU. Of those with comorbidities, the most common were hypertension and diabetes.…”
Section: Baseline Personal and Clinical Characteristics Of Patientssupporting
confidence: 92%
“…In addition, our data shows that more than half of patients admitted from the emergency room, The present results are in the same line with (Amalraj et al, 2017) who reported that most of their patients were admitted to ICU directly from the emergency room and a few were admission in ICU from the wards/rooms. Regarding comorbidities, our present study shows that the majority of patients had no identifiable comorbidities prior to ICU admission, this finding congruence with a prospective observational study by (Sulieman, et al, 2018) who found that majority of patients had no comorbidities before admission to the ICU. Of those with comorbidities, the most common were hypertension and diabetes.…”
Section: Baseline Personal and Clinical Characteristics Of Patientssupporting
confidence: 92%
“…The average days a patient was admitted in the hospital were 8.77 ± 5.37. This length of stay was reasonable for ICUs' patients when compared to other research studies (Sulieman, 2018) (Merzougui, 2018). Patients suffering from cardiovascular, nervous, cerebrovascular or multiple diseases usually have significantly higher length of stay.…”
Section: Discussionsupporting
confidence: 53%
“…The length of ICU stay was 10.3 days, similar to a regional adult ICU study length of stay of 11.8 days. [25] Other South African studies have shown disparate results [26,27] reflecting differing predominance of HIVpositive patients or surgical populations. In the secondary analysis of the 159 patients with known HIV status, HIV-negative patients had statistically significant higher APACHE II scores than HIV-positive patients.…”
Section: Excluded N=69mentioning
confidence: 99%